SISTEM INFORMASI PEMENUHAN NILAI GIZI MAKANAN IBU HAMIL DENGAN METODE COOPER BERBASIS ANDROID STUDI KASUS: PUSKESMAS MRANGGEN II - Ahmad Ashifuddin Aqham; Zaenal Mustofa; Wiwid Wahyudi (LPPM Politeknik Pratama, 2021)
Nutrition and nutrition of pregnant women is an important thing that must be met during pregnancy. The risk to the health of the fetus being conceived and the mother who is pregnant will be reduced if pregnant women get balanced nutrition and nutrition. Pregnant women who are malnourished can lead to premature birth, fetal death, abnormalities of the baby's central nervous system, as well as abnormal development, congenital defects, anemia in infants, low birth weight, and newborns with low health status.The problem that often arises today is the lack of knowledge of pregnant women about the importance of fulfilling nutrition / nutrition for pregnant women. Due to the lack of information and education of pregnant women. This study, designed a system for fulfilling the nutritional value of food for pregnant women using the Android-based COOPER method. Aims to make it easier for pregnant women to find information about nutritional intake through the selection of food menus.The author uses the Cooper method, because this method is very suitable for calculating the number of calories needed by pregnant women. The Cooper method calculates the number of calories by processing the ideal weight of pregnant women, the activities of pregnant women, and the number of hours of sleep pregnant women according to Poedysmoro (2005).To solve the problems above, it is necessary to design an Android-based information system application for the fulfillment of the nutritional value of pregnant women's food which is expected to help the role of the community, making it easier for pregnant women to find information about nutritional intake through the selection of food menus. This information can later be accessed by pregnant women to find out the fulfillment of nutrition through the food menu that must be consumed. Through the Android display that offers solutions so that it can be done anytime and anywhere.